THE MEANINGFUL MEANINGS OF KEY IMAGES IN THE LYRICS OF THE BEGINNING 21ST CENTURY - Векуа, Оксана (Modern engineering and innovative technologies, 2022)
The dominant feature of the lyrics of the beginning of the 21st century. becomes philosophical, the presence of irony and self-irony, filled with military vocabulary, as well as the rejection of the messianic pose of the creator-prophet, even from the po